THE IMPACT OF FX (FOREIGN CURRENCY EXCHANGE) ON THE BOTTOM LINE OF TEXTILE/SHOES INDUSTRIES LISTED IN INDONESIA STOCK EXCHANGE 2006-2008 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
During 2006-2008, Indonesia has been experiencing depreciation of IDR against world currency US$. The situation was triggered by global crisis October 2008, and IDR currency plunged Furthermore, 17 textile/shoes industries publicly listed in ISX have been severely hit by depreciation of IDR The "Huge Loss of Bottom Line" in 2008 was recorded (IDR 617 billions) more than half of trillion /DR. To be curious the most of industry are manufacturer-exporter. Year 2007, national textile industry overwhelmingly reports the export sales of US$ 10.05 billion and the raw material import was US$ 2.04 billions. By these facts, Income contribution from textile/shoes industries sector was US$ 8.01 billion and became a mile stone of the achievement. Depreciation of IDR currency is an advantage to the exporter as product become cheaperfor foreign buyer while import goods costly to foreign seller. The aim of this research is to describe the impact of FX on the bottom line of the Textile/Shoes Industries listed in ISX during 2006-2008, a period when the profit performance has been fallen sharply in line with the depreciation of IDR currency. By using the mathematical regression equation is surprisingly proven that FX adversely impact to the "bottom line" of the industry. The equation model selected Net Income as dependent variable while Operating Profit, Financial Charges and FX (Forex) as the independent variable. From the outcom.e of the research, the dilemma between operation and financial leverage is revealed Depreciation IDR was negatively reduced the "bottom line" this was mainly due to higher FX loss. By the end of December 2008, 17 shoes/textile industries have been suffered a huge loss of FX and recorded FX Loss (IDR 564 billions), in connection with "highfinancial leverage denominated in US$ currency". The snapshot of balance sheet position is called "Net Short Asset to US $ ". Only 5 Industries were making money among 17 industries during 2008. Only one company had already "hedged" their exposure to FX Only one company who reported profit show "debt to equity ratio" is much lower than average industry (US Textile Manufacturing) However, under the operational expectation, the depreciation of IDR currency encourage better performance of "export oriented company". This is the dilemma that textile/shoes industries have been exposed to financial risk in one side and on the other side operational risk (competitiveness)